Delineating Site‐Specific Management Zones and Evaluating Soil Water Temporal Dynamics in a Farmer's Field in Kentucky - Reyes, J. (2020)
The set of direct and indirect observations included clay and silt content, apparent electrical conductivity, soil chemical properties (pH; organic matter; and total N, P, K, Ca, Mg, and Zn), satellite‐based normalized difference vegetation index (NDVI), and lidar‐based topographic variables in a western Kentucky field. Several key variables and their capability to describe spatial crop yield variability were identified by using principal component analysis: soil clay content, slope, soil organic matter content, topographic wetness index, and NDVI. Two types of cluster analysis were applied to delineate management zones. The cluster analyses revealed that two to three zones was the optimal number of classes based on different criteria. Delineated zones were evaluated and revealed significant differences in corn (Zea mays L.) yield and temporally different soil moisture dynamics. The results demonstrate the ability of the proposed procedure to delineate a farmer's field into zones based on spatially varying soil and crop properties that should be considered for irrigation management.